Selective etching solution of carbon-doped silicon nitride / silicon oxide

By preparing a selective etching liquid of specific composition, the problem of etching SiCN materials with carbon doping exceeding 10% is solved, efficient etching and selective etching of silicon oxide is achieved, the stability and performance of the etching liquid are improved, and the semiconductor process is met demand.

CN119120026AActive Publication Date: 2024-12-13HUBEI SINOPHORUS ELECTRONIC MATERIALS CO LTD

Patent Information

Application Number
CN202411072953.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2024-12-13
Estimated Expiration
2044-08-06

AI Technical Summary

Technical Problem

The prior art cannot effectively etch silicon carbon silicon nitride (SiCN) materials with carbon doping amounts greater than 10%, and the selective etching performance of silicon oxide is insufficient, resulting in a reduced etching rate and cannot meet the needs of semiconductor processes.

Method used

SiCN materials with carbon doping amount of 10~20%, and preparation includes 50~90% catalyst, 1~10% oxidizing substances, 2~10% fluorine-containing compounds, 0.1~1% fluorine ion stabilizer and 0.1~1% Selective additives Selective etching solution, by optimizing the combination of formulation and additives, the etching rate and selection ratio are controlled.

Benefits of technology

The stable etching of SiCN materials with carbon doping amount greater than 10% is achieved, the etching rate is controlled at about 20A/min, and the selection ratio of silicon oxide is improved, and the stability and etching performance of the etching liquid are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses selective etching liquid of carbon-doped silicon nitride / silicon oxide. The selective etching liquid comprises the following raw materials in percentage by mass: 50-80% of a catalyst substance and 1-10% of an oxidizing substance, 2-10% of a fluorine-containing compound, 0.1-1% of a fluorine ion stabilizer and 0.1-1% of a selective additive; and the balance of deionized water. The etching solution can increase the etching rate of carbon-doped silicon nitride to a certain level and maintain the selection ratio of 5: 1 to silicon oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic chemicals, and in particular relates to a carbon-doped silicon nitride / silicon oxide selective etching solution. Background Art

[0002] Silicon carbon nitride (SiCN) is a semiconductor material composed of a ternary compound of silicon, carbon and nitrogen, which has the excellent optical, electrical, magnetic, thermodynamic and mechanical properties of both silicon carbide and silicon nitride. SiCN material has low cost of growth on silicon substrate and good compatibility with ultra-large-scale integrated circuits. These characteristics make SiCN one of the preferred materials for optoelectronic devices, with good economic and social benefits.

[0003] With the increase of C doping content, the corrosion resistance of SiCN gradually increases. Due to this property, it can be used as a barrier layer in semiconductor wet applications. After completing the process, it is generally removed with an etching solution. There is currently no relevant information to support the removal of SiCN. Removal of SiCN also requires a barrier layer to protect the remaining wafers. This is an urgent problem to be solved in future semiconductor processes. Therefore, a product with a certain etching rate and a certain selectivity for silicon oxide as a barrier layer is crucial.

[0004] In the SiCN film layer, the carbon doping ratio is about 1~10%. For the film layer with a lower carbon doping content, DHF solution can be used for etching. The etching rate decreases with the increase of carbon doping content. When the carbon content exceeds 10%, the etching rate approaches 0 infinitely, and there is no obvious selectivity for silicon oxide. The selectivity is about 1 / 150. Even if an oxidant is added, the above requirements cannot be achieved.

[0005] In the process of screening etching solutions, the present invention found that the material has excellent corrosion resistance and cannot be etched by conventional etching solutions. The common etching solutions in the market cannot have fast and stable etching performance. Therefore, careful and in-depth research is required from principle to experiment. The present invention selects the relevant raw materials of the present invention to control the etching rate of the SiCN film layer with a carbon doping amount greater than 10% to about 20A / min, has a selectivity of 5:1 to silicon oxide, and the solution stability can be maintained for 12 hours. Summary of the invention

[0006] In view of the above technical problems, the present invention provides a carbon-doped silicon nitride / silicon oxide selective etching solution.

[0007] In order to achieve the above object, the present invention provides a carbon-doped silicon nitride / silicon oxide selective etching solution, characterized in that: (1) the carbon doping amount of the carbon-doped silicon nitride is 10-20%; (2) it comprises the following raw materials in mass percentage: 50~90% catalyst material; 1~10% oxidizing substances; 2~10% fluorine-containing compounds; 0.1~1% fluoride ion stabilizer; 0.1~1% selective additives; The balance was deionized water.

[0008] Preferably, the carbon doping amount of the carbon-doped silicon nitride is 10-20%, preferably 10%, 15% and 20%. As the carbon doping amount increases, the etching difficulty increases exponentially, and the requirements for the etching solution are also higher. The present invention ultimately uses SiCN with a carbon doping amount of 20%.

[0009] Preferably, the catalyst substance is an aqueous solution with a mass fraction of 70-90%.

[0010] More preferably, the alkaline substance is any one of aqueous solutions of sulfuric acid, phosphoric acid, acetic acid, boric acid, citric acid, oxalic acid, and maleic acid.

[0011] The addition of the catalyst in the present invention can significantly reduce the activation energy during the reaction and increase the etching rate.

[0012] Preferably, the oxidant is an aqueous solution with a mass fraction of 10-30%.

[0013] More preferably, the oxidant is any one of sodium hypochlorite, potassium hypochlorite, potassium permanganate, hydrogen peroxide, ammonium persulfate, and an aqueous solution of nitric acid.

[0014] The addition of the oxidant of the present invention can, on the one hand, increase the etching rate and accelerate the reaction process by oxidizing the film layer; on the other hand, the oxidant will not oxidize silicon oxide, which can indirectly increase the selectivity.

[0015] Preferably, the fluorine-containing compound is an aqueous solution with a mass fraction of 15-35%.

[0016] More preferably, the fluorine-containing compound is any one of an aqueous solution of ammonium fluoride, ammonium bifluoride, hydrofluoric acid, and tetrabutylammonium fluoride.

[0017] The addition of the fluorine-containing compound of the present invention can significantly increase the etching rate, reduce the etching rate of the silicon-containing compound therein, and can react with the subsequent selector to increase the selectivity.

[0018] Preferably, the fluoride ion stabilizer is any one of sodium borate, niobium chloride and titanium oxalate.

[0019] The present invention adopts high temperature etching conditions, which will accelerate the escape of fluoride ions. With the addition of fluoride ion stabilizer, a complex structure can be formed with fluoride ions, thereby reducing the escape rate of fluoride ions and greatly improving the life of the solution.

[0020] Preferably, the selective additive is any one of ureapropyltriethoxysilane, mercaptopropyltriethoxysilane, aminopropyltriethoxysilane, aminoethylaminoisobutylmethyldimethoxysilane, and N-[3-(trimethoxysilyl)propyl]butan-1-amine.

[0021] The present invention adopts the corresponding silane, which has a significant inhibitory effect on the etching rate of silicon oxide and can react with fluorine ions to improve the selectivity.

[0022] The beneficial effects of the present invention are: 1. In this experiment, carbon-doped silicon nitride was etched. The material has super strong etching resistance. The present invention can etch the material and has a certain etching rate, which can be regulated.

[0023] 2. Under the premise of ensuring the etching rate, the silicon oxide film layer can be added as a barrier layer, which provides a certain basis for its application.

[0024] 3. The addition of fluoride ion stabilizer in the etching solution gives it a longer life and increased stability. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is further explained below in conjunction with specific embodiments. It is worth noting that the following embodiments are only preferred embodiments of the present invention and should not be construed as limiting the present invention. The protection scope of the present invention shall be subject to the contents recorded in the claims. Any modification or replacement made by a person skilled in the art to the technical solution of the present invention without creative work shall fall within the protection scope of the present invention.

[0026] Note: In order to verify the selectivity of 1.0% to 10% carbon-doped silicon nitride and 10% to 20% carbon-doped silicon nitride in DMF and DHF oxidant solutions mentioned in the background of the present invention, Example 1 and Comparative Examples 6, 7, and 8 were used to etch silicon oxide at the same time, respectively, on 5% carbon-doped SiCN and 20% carbon-doped SiCN used in the present invention.

[0027] Example 1 A selective etching solution for carbon-doped silicon nitride / silicon oxide, in this embodiment, a carbon-doped silicon nitride silicon wafer with a carbon doping amount of 10% is selected, and its formula is: 55% phosphoric acid aqueous solution (mass fraction is 89%), 4% sodium hypochlorite solution (mass fraction is 20%), 6% ammonium fluoride aqueous solution (mass fraction is 25%), 0.5% sodium borate, 0.2% ureapropyl triethoxysilane, and the rest is deionized water.

[0028] Example 2 A selective etching solution for carbon-doped silicon nitride / silicon oxide, in this embodiment, a carbon-doped silicon nitride silicon wafer with a carbon doping amount of 15% is selected, and its formula is: 65% acetic acid aqueous solution (mass fraction is 85%), 5% potassium hypochlorite aqueous solution (mass fraction is 10%), 1.2% ammonium bifluoride aqueous solution (mass fraction is 35%), 0.7% sodium borate, 0.01% mercaptopropyl triethoxysilane, and the rest is deionized water.

[0029] Example 3 A selective etching solution for carbon-doped silicon nitride / silicon oxide, in which a carbon-doped silicon nitride wafer with a carbon doping amount of 20% is selected in this embodiment, and its formula is: 75% sulfuric acid aqueous solution (mass fraction is 78%), 7% potassium permanganate aqueous solution (mass fraction is 15%), 1.5% tetrabutylammonium fluoride aqueous solution (mass fraction is 23%), 0.7% niobium chloride, 0.01% N-[3-(trimethoxysilyl)propyl]butyl-1-amine, and the rest is deionized water.

[0030] Example 4 A selective etching solution for carbon-doped silicon nitride / silicon oxide, in this embodiment, a carbon-doped silicon nitride silicon wafer with a carbon doping amount of 10% is selected, and its formula is: 70% boric acid aqueous solution (mass fraction is 80%), 5% hydrogen peroxide aqueous solution (mass fraction is 12%), 2% hydrofluoric acid aqueous solution (mass fraction is 15%), 0.8% titanium oxalate, 0.01% aminopropyltriethoxysilane, and the rest is deionized water.

[0031] Example 5 A selective etching solution for carbon-doped silicon nitride / silicon oxide, in this embodiment, a carbon-doped silicon nitride wafer with a carbon doping amount of 15% is selected, and its formula is: 60% citric acid solution (mass fraction is 18%), 7% nitric acid aqueous solution (mass fraction is 14%), 3.5% hydrofluoric acid aqueous solution (mass fraction is 25%), 0.7% niobium chloride, 0.02% aminoethylaminoisobutylmethyldimethoxysilane, and the rest is deionized water.

[0032] Example 6 A selective etching solution for carbon-doped silicon nitride / silicon oxide, in this embodiment, a carbon-doped silicon nitride silicon wafer with a carbon doping amount of 20% is selected, and its formula is: 75% oxalic acid aqueous solution (mass fraction is 19%), 4% ammonium persulfate aqueous solution (mass fraction is 12%), 1% tetrabutylammonium fluoride aqueous solution (mass fraction is 15%), 0.6% titanium oxalate, 0.02% ureapropyltriethoxysilane, and the rest is deionized water.

[0033] Example 7 A selective etching solution for carbon-doped silicon nitride / silicon oxide, in this embodiment, a carbon-doped silicon nitride silicon wafer with a carbon doping amount of 10% is selected, and its formula is: 80% maleic acid aqueous solution (mass fraction is 20%), 8% ammonium persulfate aqueous solution (mass fraction is 20%), 1% tetrabutylammonium fluoride aqueous solution (mass fraction is 30%), 1% sodium borate, 0.02% ureapropyltriethoxysilane, and the rest is deionized water.

[0034] Comparative Example 1 A carbon nitride / silicon oxide doped selective etching solution, the formula of which is the same as that of Example 6, except that the oxalic acid aqueous solution is not added.

[0035] Comparative Example 2 A carbonitride / silicon oxide doped selective etching solution, the formula of which is the same as that of Example 6, except that the ammonium persulfate aqueous solution is not added.

[0036] Comparative Example 3 A carbon nitride / silicon oxide doped selective etching solution, the formula of which is the same as that of Example 6, except that the tetrabutylammonium fluoride aqueous solution is not added.

[0037] Comparative Example 4 A carbon nitride / silicon oxide doped selective etching solution, the formula of which is the same as that of Example 6, except that sodium borate is not added.

[0038] Comparative Example 5 A carbon nitride / silicon oxide doped selective etching solution, the formula of which is the same as that of Example 6, except that ureapropyltriethoxysilane is not added.

[0039] Comparative Example 6 2% HF aqueous solution was used to simultaneously etch SiCN with a carbon content of 5%, silicon oxide, and SiCN with a carbon content of 20%.

[0040] Comparative Example 7 2% HF and 0.5% HNO3 aqueous solution were used to simultaneously etch 5% carbon-doped SiCN, silicon oxide, and 20% carbon-doped SiCN.

[0041] Comparative Example 8 5% carbon-doped SiCN, silicon oxide and 20% carbon-doped SiCN were etched simultaneously using 2% HF, 0.5% HNO3 and 0.2% ureapropyltriethoxysilane aqueous solution.

[0042] Result detection: Take the carbon-doped silicon nitride and silicon oxide monolithic wafers purchased from Hynix and cut them into small pieces of 10mm×10mm and etch them as follows: Etching rate test: Place the polycrystalline silicon monolithic wafer in a 200:1 hydrofluoric acid solution at 80°C and clean it for 40s to remove the hydrolyzed oxide layer on the surface. Use an ellipsometer to measure the carbon-doped silicon nitride and silicon oxide monolithic wafers. The initial thickness of the carbon-doped silicon nitride and silicon oxide monolithic wafers is calculated by model fitting, and the average value is taken for the 4 points measured on the monolithic wafer. Then, place the carbon-doped silicon nitride monolithic wafer in the etching solution for etching for 5-10 minutes, clean it and blow it dry with nitrogen, use an ellipsometer to test the spectra of the carbon-doped silicon nitride and silicon oxide monolithic wafers (keep the test points consistent before the moment), fit the calculation and take the average value to obtain the thickness of the carbon-doped silicon nitride and silicon oxide monolithic wafers, and calculate the etching rate of the carbon-doped silicon nitride and silicon oxide monolithic wafers. The etching rates of the carbon-doped silicon nitride and silicon oxide monolithic wafers configured by the selective etching solution of the above embodiments and comparative examples can be seen in Table 1.

[0043] Table 1 Effect of etching time on etching rate of uniform etching solution formula Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 20%SiCN etching rate 25.23 23.02 35.22 45.31 28.69 19.56 17.58 5%SiCN etching rate 98.63 - - - - - - SiO2 etching rate 5.02 4.23 6.11 7.78 5.44 3.25 3.31 formula Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 20%SiCN etching rate 1.23 2.53 0.25 19.11 19.56 0.03 0.02 0.02 5%SiCN etching rate - - - - - 0.85 1.35 1.07 SiO2 etching rate 3.15 2.03 1.25 3.32 53.25 175.44 179.15 65.32 Table 2 Effect of etching stability Time / h Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 0 25.23 23.02 35.22 45.31 28.69 19.56 17.58 2 25.21 23.00 35.14 45.11 28.67 19.52 17.56 4 25.14 22.95 35.07 45.02 28.60 19.50 17.55 6 25.12 22.87 35.02 44.91 28.52 19.47 17.53 8 25.11 22.84 34.91 44.83 28.44 19.44 17.50 Time / h Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 0 1.23 2.53 0.25 19.11 19.56 2 1.23 2.50 0.25 11.21 19.49 4 1.22 2.49 0.24 5.43 19.44 6 1.20 2.44 0.24 2.12 19.40 8 1.18 2.43 0.22 2.03 19.37 As shown in Table 1, there is a significant difference in the etching rates between the etching solutions prepared in Examples 1-7 and the etching solutions prepared in Comparative Examples 1, 2, and 3, indicating that the addition of a catalyst is the key to etching polycrystalline silicon wafers, and the addition of a catalyst is more conducive to etching SiCN; Comparative Examples 6, 7, and 8 verify the relevant contents of the present invention, and Example 1 has a higher selectivity for 5% carbon-doped SiCN compared to the following Comparative Examples 6, 7, and 8, while Comparative Examples 6, 7, and 8 cannot etch 20% carbon-doped SiCN, and the etching rate is infinitely close to 0.

[0044] Compared with the stability of the uniform etching solutions prepared in Examples 1-7 and the etching solution prepared in Comparative Example 4, the addition of a fluoride ion stabilizer is more conducive to the stability of the etching solution.

[0045] Compared with the selectivity of the uniform etching solution prepared in Examples 1-7 and the etching solution prepared in Comparative Example 5, the addition of selective substances is more conducive to reducing the etching rate of silicon oxide, providing a barrier layer for the next process and laying the foundation for later applications.

Claims

1. A carbon-doped silicon nitride / silicon oxide selective etching solution, characterized in that: (1) The carbon content of carbon-doped silicon nitride is 10-20%; (2) The raw materials include the following mass percentages: 50~90% catalyst material; 1~10% oxidizing substances; 2~10% fluorine-containing compounds; 0.1~1% fluoride ion stabilizer; 0.1~1% selective additives; The balance was deionized water.

2. The selective etching solution of carbon-doped silicon nitride / silicon oxide according to claim 1, characterized in that: The carbon doping amount of the carbon-doped silicon nitride wafer is 15-20%.

3. The selective etching solution of carbon-doped silicon nitride / silicon oxide according to claim 1, characterized in that: The catalyst substance is an aqueous solution with a mass fraction of 70-90%.

4. The selective etching solution of carbon-doped silicon nitride / silicon oxide according to claim 2, characterized in that: The catalyst material is any one of 80% aqueous solutions of sulfuric acid, phosphoric acid, acetic acid, boric acid, citric acid, oxalic acid, and maleic acid.

5. The selective etching solution of carbon-doped silicon nitride / silicon oxide according to claim 1, characterized in that: The oxidant is an aqueous solution with a mass fraction of 10-30%.

6. A carbon-doped silicon nitride / silicon oxide selective etching solution according to claim 4, characterized in that: The oxidant is any one of sodium hypochlorite, potassium hypochlorite, potassium permanganate, hydrogen peroxide, ammonium persulfate, and an aqueous solution of nitric acid.

7. The selective etching solution of carbon-doped silicon nitride / silicon oxide according to claim 1, characterized in that: The fluorine-containing compound is an aqueous solution with a mass fraction of 15-35%.

8. A carbon-doped silicon nitride / silicon oxide selective etching solution according to claim 6, characterized in that: The fluorine-containing compound is any one of an aqueous solution of ammonium fluoride, ammonium bifluoride, hydrofluoric acid, and tetrabutylammonium fluoride.

9. The carbon-doped silicon nitride / silicon oxide selective etching solution according to claim 1, characterized in that: The fluoride ion stabilizer is any one of sodium borate, niobium chloride and titanium oxalate.

10. The carbon-doped silicon nitride / silicon oxide selective etching solution according to claim 1, characterized in that: The selective additive is any one of ureapropyl triethoxysilane, mercaptopropyl triethoxysilane, aminopropyl triethoxysilane, aminoethylaminoisobutylmethyldimethoxysilane, and N-[3-(trimethoxysilyl)propyl]butan-1-amine.

Citation Information

Patent Citations

  • Compositions for removal of metal hard mask etching residues from a semiconductor substrate

    CN101883688A

  • Compositions and methods for selectively etching titanium nitride

    CN104145324A

  • Nitrogen-containing compounds for etching semiconductor structures

    CN115394641A

  • Selective etching solution of silicon nitride / silicon oxide 3D NAND structural sheet

    CN115873599A

  • Uniform etching solution for polycrystalline silicon

    CN117866637A

Cited By

  • Back contact solar cell, preparation method thereof and cell module

    CN119894109A